Analysis of The Usefulness of BUMDes Funds in Klari Sub-District in 2023 - Elsa Nurmalasari; Dedi Mulyadi; Santi Pertiwi Hari Sandi (West Science Business and Management, 2024)
The regulation of Village-Owned Enterprises (BUMDes) is stated in Law No. 6 of 2014 concerning Villages article 88 paragraph 1 which states that the establishment of BUMDes is carried out through a village deliberation agreement. This research aims to find out how BUMDes funding in Klari District in 2023, find out the benefits and role of BUMDes to the community, and find out the income and results of BUMDes in Klari Sub-district in 2023. The research method used is qualitative method. Of the 13 villages in Klari sub-district, there are 5 villages with active BUMDes in 2023, namely, Belendung village with BUMDes funds of Rp. 23.256.000 has assets in the form of cages and livestock, Sumur Kondang village with BUMDes funds of Rp. 57.000.000 has a net income of Rp. 7.100.000, Walahar Village with BUMDes funds of Rp. 200.000.000 has assets in the form of bottled drinking water machines, gallons, cups, cup sealer machines, and fertilizer machines, Gintung Kerta Village with BUMDes funds derived from net income in 2023 of Rp. 6.969.120, and Duren Village with BUMDes funds of Rp. 181.672.900 has net income of Rp. 112.004.000. BUMDes that have been built, benefit the community who are included as partners who manage, maintain and develop the business. Suggestions for villages that have active BUMDes or not, to conduct training or counseling on utilizing opportunities and resources owned by each region so as to open up jobs and encourage the activeness of village communities in contributing to utilizing BUMDes funds.